SHAUN'S MISBEHAVIOR REFLECTED IN MEADOW'S THIS IS ENGLAND (2007): A BEHAVIORIST APPROACH - ASHARI, ABU (2010)
The study is about the relationship between environment and character building in Shane Meadows This Is England. The major problem in this research is how the Shaun's misbehavior is reflected in Meadow's movies This Is England. The objective of the study is to describe the structural elements of the movie and to analyze major character's misbehavior from behaviorist perspective. The writer conducts the research by using qualitative method that uses the library research, while the data sources are literary data that are divided into two categories, primary and secondary data. The primary data are the movie subtitle This Is England itself and the secondary data include several references from internet. The object of the research is the Shaun's misbehavior as the major character derived from Shane Meadows This Is England, which was released on 27th April 2007 published in United Kingdom by Optimum Releasing (UK). The outcome of the study shows the following conclusion. Firstly, there is a close relationship between a work of literature and behavior phenomena. Secondly, the behaviorist analysis falls into general conclusion that human misbehavior is influenced by interacting factors: environment. Thirdly, Shaun's misbehavior is influenced by his environment.